2020
DOI: 10.1007/s10534-020-00240-6
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization of ferric uptake regulator (Fur) from Aliivibrio salmonicida. Mapping the DNA sequence specificity through binding studies and structural modelling

Abstract: Iron is an essential nutrient for bacteria, however its propensity to form toxic hydroxyl radicals at high intracellular concentrations, requires its acquisition to be tightly regulated. Ferric uptake regulator (Fur) is a metal-dependent DNA-binding protein that acts as a transcriptional regulator in maintaining iron metabolism in bacteria and is a highly interesting target in the design of new antibacterial drugs. Fur mutants have been shown to exhibit decreased virulence in infection models. The protein inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 65 publications
(125 reference statements)
0
2
0
Order By: Relevance
“…Binding of Fur to the Fur-box protects the hin fI site from being cleaved by Hin fI ( 18 ). The restriction site protection assay has been applied to investigate the Fur-box binding activity of E. coli Fur after nitric oxide exposure ( 28 ), of the Co(II)-bound Helicobacter pylori Fur ( 21 ), and of the Mn(II)-bound Aliivibrio salmonicida Fur ( 29 ). For the experiments, the promoter sequence of the operon iucABCD was synthesized (GenScript co) and inserted into plasmid pUC19 to create pUC19- iuc ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Binding of Fur to the Fur-box protects the hin fI site from being cleaved by Hin fI ( 18 ). The restriction site protection assay has been applied to investigate the Fur-box binding activity of E. coli Fur after nitric oxide exposure ( 28 ), of the Co(II)-bound Helicobacter pylori Fur ( 21 ), and of the Mn(II)-bound Aliivibrio salmonicida Fur ( 29 ). For the experiments, the promoter sequence of the operon iucABCD was synthesized (GenScript co) and inserted into plasmid pUC19 to create pUC19- iuc ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the only transcriptional regulator up-expressed under Cr(VI) was Fur, which is involved in iron homeostasis in response to changes in intracellular levels of Fe 2+ , this last is an indirect chemical Cr(VI) reductants under aerobic environmental conditions(Troxell and Hassan 2013;Bansal et al 2019;Bellenberg et al 2019). Noticeably, Fur was originally described as a repressor of genes involved in iron uptake, storage and metabolism(Berg et al 2020). Recent studies however, have indicated that Fur may also function as an activator(Butcher et al 2012).…”
mentioning
confidence: 99%